The risk factor of metastatic status of retinoblastoma patient in Yogyakarta Tertiary Hospital - Agus Supartoto; Sri Nawung Hartanti; Banu Aji Dibyasakti; Purjanto Tepo Utomo; Datu Respatika; Muhammad Bayu Sasongko (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2020)
The metastases of the tumor become a serious problem malignancy including retinoblastoma. This study aimed to observe the correlation between several risk factors with the metastatic status of retinoblastoma patients in Yogyakarta Tertiary Hospital. Records of patients with retinoblastoma treated between 2011 and 2017 were obtained for observational analytic study. The gender, laterality, age, Body Mass Index (BMI) classification, BMI for age, type of retinoblastoma, and metastatic status were analyzed. The association was statistically analyzed by the correlation ratio of Eta test. Thirty-seven cases of retinoblastoma were enrolled in this study, with mean age 29.44 (±14.1) months; 14 females and 23 males. Ten patients (27.0%) have no metastases, while 27 patients (72.9%) exhibit metastases. The multivariate logistic regression analysis demonstrated that male gender (OR 8.3; 95% CI 1.07–64.5; p = 0.04) and age below 24 months (OR 17.6; 95% CI 1.26-248.31; p = 0.03) were a predictive of the metastatic status for retinoblastoma. On the other hand, the laterality, BMI classification, BMI for age, and types of retinoblastoma were not associated with the metastatic status of retinoblastoma. The gender and age were significantly associated with the metastatic status of retinoblastoma. Male patients and age below 24 months were more likely to have metastatic disease of retinoblastoma.